Mo(AlxSi1−x)2 healing particles for high temperature ceramics and encapsulation by selective oxidation of aluminium - Zhaoying Ding; Johannes C. Brouwer; Cees Kwakernaak; Jia-Ning Zhu; Vera Popovich; Marcel J.M. Hermans; Willem G. Sloof (Materials & Design, 2023)
To prevent premature triggering of the healing reaction in Mo-Si containing self-healing thermal barrier coating system, an oxygen impenetrable shell (α-Al2O3) around the sacrificial healing particles (MoSi2) is desired. Here an encapsulation method is presented through selective oxidation of Al in Mo(AlxSi1-x)2 particles. Healing particles of Mo(AlxSi1-x)2 is designed in terms of alumina shell thickness, particle size and fraction Al dissolved. By replacing Si by Al in MoSi2 up to the maximum solubility (x = 0.65) a strong crack healing ability is maintained (relative volume expansion ≥ 40 %). The formed exclusive α-Al2O3, featuring a two-layered structure, results from a counter-diffusion process along the grain boundaries, and its oxidation kinetics fits well with the 3D diffusion-Jander model. After 16 h exposure in gaseous ambient with a pO2 of 5 × 10-10 atm. at 1100 °C, a closed and dense shell of α-Al2O3 is formed with a thickness of about 1.3 µm. The oxide shell produced under this condition provided healing particles with significantly improved stability upon exposure to high pO2 of 0.2 atm. at 1100 °C for 50 h. The particles after exposure feature an inner core of MoSi2 with Al completely consumed and an oxide shell of α-Al2O3.